Speed and Sustainability When Entering New Market - Gwang Seok Kim (MDPI AG, 2021)
When constructing a factory to enter new markets, the optimal size to respond to demand is determined by the construction time. Hyundai Motor Company (Hyundai), on the other hand, standardizes the size of its factories to speed up the entry and response to demand. The Hyundai’s entry mode, called SPEED, is modeled as a strategy. The strategy is evaluated of excellence with capacity expansion rules formalized, key parameters identified, and mathematical programming. The SPEED strategy is suited for market followers who want to enter a midscale or mature market in terms of business excellence and more sustainable throughout the factory’s life cycle on the side of sustainability. Shorter construction times, as a result of the SPEED strategy, can help to prevent environmental damage while also standardization can increase job prospects for local workers.